Assessing the Influence of COVID‐19 on the Shortwave Radiative Fluxes Over the East Asian Marginal Seas. Issue 3 (2nd February 2021) - Ming, Yi; Loeb, Norman G.; Lin, Pu; Shen, Zhaoyi; Naik, Vaishali; Singer, Clare E.; Ward, Ryan X.; Paulot, Fabien; Zhang, Zhibo; Bellouin, Nicolas; Horowitz, Larry W.; Ginoux, Paul A.; et al.
Abstract: The Coronavirus Disease 2019 (COVID‐19) pandemic led to a widespread reduction in aerosol emissions. Using satellite observations and climate model simulations, we study the underlying mechanisms of the large decreases in solar clear‐sky reflection (3.8 W m −2 or 7%) and aerosol optical depth (0.16 W m −2 or 32%) observed over the East Asian Marginal Seas in March 2020. By separating the impacts from meteorology and emissions in the model simulations, we find that about one‐third of the clear‐sky anomalies can be attributed to pandemic‐related emission reductions, and the rest to weather variability and long‐term emission trends. The model is skillful at reproducing the observed interannual variations in solar all‐sky reflection, but no COVID‐19 signal is discerned. The current observational and modeling capabilities will be critical for monitoring, understanding, and predicting the radiative forcing and climate impacts of the ongoing crisis. Plain Language Summary: Satellite data showed large reductions in reflected sunlight and aerosol optical depth over clear (cloudless) sky off the East Asian coast in March 2020. Although these changes are consistent with a sharp cut in aerosol emissions due to the lockdown put in place to curb the spread of Coronavirus Disease 2019 (COVID‐19), one cannot rule out possible roles played by weather conditions such as winds and humidity. We use a climate model forced with past known weather to isolate the latter factor, and to describe the difference from the observation to the former. The main finding is that the pandemic‐related emission reductions are responsible for about one‐third of the observed signal. The model can largely reproduce the year‐to‐year variations in all‐sky reflection, but no influence of COVID‐19 is detected. Key Points: Solar clear‐sky reflection was observed to drop substantially over the East Asian Marginal Seas in March 2020 Climate model simulations nudged with reanalysis data are used to separate the impacts of meteorology and emissions It is found that about one‐third of the clear‐sky anomalies can be attributed to pandemic‐related emission reductions